A state-of-the-art review on experimental investigation and finite element analysis on structural behaviour of fibre reinforced polymer reinforced concrete beams. Issue 3 (March 2023) - Solahuddin, B.A.; Yahaya, F.M.
Abstract: Fibre reinforced polymer (FRP) composite is a useful material. It has been utilised to enhance the structural behaviour of reinforced concrete beams (RCB). It is also crucial to summarise the impact of FRP on various types of RCB properties. This study summarises the FRP usage's impact on the RCB's structural behaviour based on previous research by reviewing and discussing the experimental study and finite element analysis (FEA) results. Based on previous relevant literature reviews, the experimental investigation and FEA showed significant improvements in flexure, stiffness, young modulus, load-deflection, ultimate load capacity, fracture pattern, and failure mode when FRP was used in RCB production. This FRP composite material can be used as the external reinforcement for RCB due to its high strength capability, force, load, and corrosion resistance with adhesive and anchorage properties. Using FRP in RCB can benefit civil engineering by increasing its structural behaviour and performance, especially in construction industry.